Diagnostic accuracy of positron emission tomography/computerized tomography for periprosthetic joint infection of hip: systematic review and meta-analysis - Hongning Hua; Jinwen Liu (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background American Academy of Orthopaedic Surgeons (AAOS) has provided the guidelines for diagnosing a patient with periprosthetic joint infection including the use of positron emission tomography/computed tomography (PET/CT). Systematic evidence focussing on periprosthetic joint infection (PJI) of hip is limited, which also contains limited number of studies. Hence, the current study aims to perform a pooled analysis of all studies that have assessed the diagnostic accuracy of PET/CT for PJI of hip. Methods Searches were done in PubMed Central, EMBASE, MEDLINE, SCOPUS and Cochrane library until December 2022. Meta-analysis was carried out using random-effects model. With 95% confidence intervals (CIs), pooled sensitivity and specificity were reported. Results Twenty-six studies met the inclusion criteria. The pooled sensitivity of PET/CT was 89% (95% CI 84–93%), while the pooled specificity was 86% (95% CI 79–91%). The AUROC was 0.94 (95% CI 0.72–0.99). There was statistically significant heterogeneity (p < 0.001) with I2 value of 96%. The diagnostic odds ratio was 52 (95% CI 26–106). Likelihood ratio positive was 6.5 (95% CI 4.1–10.3) and negative was 0.13 (95% CI 0.08–0.19). Conclusion Our study found that PET/CT was found to have higher level of accuracy in terms of sensitivity and specificity. Further large-scale research can help to find answers for such questions and provide final conclusive evidence on the inclusion of the imaging modality into the routine clinical practice guidelines for suspected periprosthetic joint infection patients.